Lavadeiras, cozinheiras e amas de leite. O cotidiano das trabalhadoras domésticas em Fortaleza (1920-1940) - Linhares, Juliana Magalhães (2021)
This work examines the daily lives of paid domestic workers in Fortaleza during the 1920s and 1940s to understand who these historical subjects were and how they lived in the post-abolition period. It also seeks to identify patterns of servile continuity in labor relations. The study places the context of the 1920s and 1940s as a period of political and social discussions, encompassing not only labor rights but also women's rights, such as minimum wage and maternity leave. By observing the role of domestic workers within the new urban dynamics and the creation of networks of solidarity and sociability as forms of resistance and adaptation, various aspects related to work arrangements, family honor, race, and gender come to light. The analysis was conducted through the examination of sources such as newspapers, criminal cases, censuses, and civil and penal legislation. It is concluded that the lives of domestic workers were marked by the precarization of social relations, often governed by unstable or nonexistent contracts. Urban poor female workers were relegated to unskilled positions with low wages. Their experiences and daily lives reveal the gap between labor rights advancements and the reality of informality and non-work. Even after an initial attempt at unionization of domestic workers, they remained outside the professional categories protected by labor laws. Therefore, for these women, maintaining some networks of solidarity was necessary to survive the precarious conditions of life and work.